Cultivating intercultural competences in digital higher education through English as an international language - Nguyen, Ha; Dolan, Hilary; Taylor, Samuel; Peyretti, Thomas (Journal of Academic Language and Learning, 2022)
Intercultural competences (IC), which underscore the ability to recognise, value and work with cultural diversity, play a key role in academic, career and social-emotional development in a globalised world. Higher education needs to help students cultivate IC, and digital education offers an alternative space for engaging with difference. Our research integrates holistic IC models to promote ongoing, dynamic intercultural learning. We also explore the role of adopting English as an international language (EIL) in developing IC. In Australia, the native-speaker model of English has contributed to a divide that works against other English users. Shifting to an EIL paradigm can empower all students to take ownership of English and participate with confidence in intercultural communication. Through a systematic literature review on the development of IC and the use of EIL, we found that cultivating students’ IC requires a complex view of culture and identity towards greater social cohesion. Here, enhancing learners’ digital literacies is an enabling factor. Our research also highlights the critical role of EIL in celebrating diversity and prioritising the purpose of English over form. EIL practices can transform teachers’ and learners’ self-beliefs and relocate culture from a reified view towards more sophisticated understandings. Based on our findings, we propose practical steps institutions and educators can take to cultivate IC in their students.